Earthquake hypocenters and focal mechanisms in central Oklahoma reveal a complex system of reactivated subsurface strike‐slip faulting. Issue 8 (23rd April 2015) - McNamara, D. E.; Benz, H. M.; Herrmann, R. B.; Bergman, E. A.; Earle, P.; Holland, A.; Baldwin, R.; Gassner, A.
Abstract The sharp increase in seismicity over a broad region of central Oklahoma has raised concern regarding the source of the activity and its potential hazard to local communities and energy industry infrastructure. Since early 2010, numerous organizations have deployed temporary portable seismic stations in central Oklahoma in order to record the evolving seismicity. In this study, we apply a multiple‐event relocation method to produce a catalog of 3639 central Oklahoma earthquakes from late 2009 through 2014. Regional moment tensor (RMT) source parameters were determined for 195 of the largest and best recorded earthquakes. Combining RMT results with relocated seismicity enabled us to determine the length, depth, and style of faulting occurring on reactivated subsurface fault systems. Results show that the majority of earthquakes occur on near‐vertical, optimally oriented (NE‐SW and NW‐SE), strike‐slip faults in the shallow crystalline basement. These are necessary first‐order observations required to assess the potential hazards of individual faults in Oklahoma.